Implementasi Filsafat Sosial Marhaenisme Untuk Membentuk Masyarakat Yang Plural Menuju Indonesia Emas - Lukman Fauzi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Soekarno was first President of Indonesia has more ideas and concepts for social development. Since young lifespan, Soekarno was showed his attention for Indonesia freedom. As HOS. Tjokroaminoto’s Student, Soekarno has good rhetoric to interest other people in order follow his thought. One of Soekarno’s thought is Marhaenism. Marhaenism as struggle coordinating institution for strive with colonial government. Soekarno founds this idea with he meets a poor farmer which named Marhaen. After Soekarno meets Marhaen, he found that more Indonesia people were under poverty has caused colonialism. Soekarno had arranged the Marhaenism principals as struggle law for Marhaenis. Marhaenis are the poor farmer, laborer, and other poor people that need freedom in their life. Moreover, Marhaenism is critical theory to analyst all thinking’s which contains hidden exploitation, like thinking doctrine or hidden political action was masked by religion thought. As critical theory, Marhaenism is being epistemology based rationally critic. To critic other thinking, marhaenism principles become linguistic study to analyst and interprets about ides or concepts were be exclusive ideology. Soekarno in his some writings criticizes other exclusive ideology was closed critic reason for development and progression. For Soekarno, critic reason is very important as human being. Without reason, a human can’t grow up in their life. This attention was understood by Soekarno when he knew the reality of Indonesia people under colonialize. And now, marhaenism as a critic thingking purposed to apply Pancasila as Indonesia Ideology. Pancasila was defined by Soekarno with Marhaenism view. So, the spirit of Soekarno in Marhaenism principles always needed to apply Pancasila in social life for Indonesia development.